Investigating the relationship between toxic parents and self-esteem in elementary school students - Fidrayani, Fidrayani; Serojaningtyas, Meidy (Journal of Integrated Elementary Education, 2023)
This study aims to explore the correlation between the behavior of "toxic parents" and the self-esteem of elementary school students. The research adopts a quantitative approach with a correlation method and involves a total of 90 respondents, comprising 9 fathers, 81 mothers, 52 male students, and 38 female students, selected using a quota sampling technique. Data collection is carried out through carefully designed questionnaires, and hypothesis testing is conducted using product-moment correlation analysis. The study's results reveal a correlation value (r) of -0.484, surpassing the critical value (r table) of 0.207, with a significance level (p) of 0.000, which is lower than 0.05. Additionally, the coefficient of determination at 23.42% signifies a substantial influence of "toxic parents" behavior on the self-esteem of students. These findings unequivocally confirm a significant negative relationship between "toxic parent" behavior and students' self-esteem. The implication is a pressing need for fostering positive and supportive parenting approaches as a potential avenue for positively impacting the self-esteem development of elementary school students.